Mengakarkan Nilai Pertobatan Kristiani dalam Ritus Oke Saki - Sianturi, Ian Jovi; Teon, Mario Constantino; Makul, Rafael (Perspektif, 2023)
This study aims to discuss the Oke Saki ritual and how this ritual can be a means of instilling Catholic values among Manggarai Catholics themselves. The new understanding in the Catholic Church that recognizes that there are seeds of goodness and salvation in other religions and cultures makes the Church aware of the importance of rooting faith in local culture. This re[1]search uses a qualitative research method with an ethnographic design. Pri[1]mary data was collected from interview and observation. The concept of the Oke Saki ritual has similarities to the sacrament of confession, as both involve human efforts, repentance for sins and mistakes committed. How[1]ever, there are also significant differences, one of which is that Oke Saki emphasizes collective sin while Catholicism emphasizes personal sin and re[1]pentance. The Church cares about collective sin, but personal repentance should be prioritized. Because of this similarity, the Oke Saki ritual can be integrated with the liturgy of the sacrament of confession. However, further study is still needed due to different understandings. Efforts are needed to purify understandings that are contrary to faith, especially those that dis[1]credit God’s dominion over all of His creation. This is a way to root Catholic values in culture while preserving local cultural treasures.